Competence development in start-ups and SMEs: what is the role of higher education institutions as cooperation partners?. (1st January 2011) - Kailer, Norbert; Thum-Kraft, Monika
Competence development is a key competitive factor for small and medium-sized enterprises (SMEs). In the last few years, cooperation schemes between SMEs and higher education institutions (HEIs) have increased in quantity and intensity. The online survey among 4, 050 Austrian companies examines the role of HEIs as cooperation partners in corporate competence development for SMEs and shows that cooperation with HEIs depends on the firm size. SMEs see the target group for HEIs mainly on management level, young executives, and specialists. Companies cooperate with HEIs mainly to keep specialist knowledge updated, to improve their access to students as potential future staff members and to increase their reputation. The initiative for cooperation projects is taken by company staff rather than by HEIs. SMEs' main selection criteria are a high degree of practical experience and didactic qualifications of the staff as well as a flexible programme provision.